Ischemic postconditioning ameliorates diabetic cerebral ischemia via activating the brain-derived neurotrophic factor–tropomyosin receptor kinase B–hypoxia-inducible factor 1α–Bcl-2/adenovirus E1B 19-kDa-interacting protein 3 pathway to induce microglial mitophagy and suppress A1 astrocyte-mediated neuroinflammation - Zhao, Ling; Han, Yuanyuan; Wang, Ying; Ke, Tingyu; Huang, Shiying (Frontiers in Endocrinology, 2025)
AimDiabetes mellitus exacerbates cerebral ischemic injury. However, effective interventions remain limited. Ischemic postconditioning (IPOC) is a potential neuroprotective strategy; however, its efficacy and mechanisms in diabetes remain poorly understood. This study aimed to explore the therapeutic effects and underlying mechanisms of IPOC in diabetes complicated by cerebral ischemia.MethodsTree shrews with diabetes complicated by cerebral ischemia were used as the study subjects and were subjected to a standardized IPOC intervention protocol.ResultsThe results showed that compared with the control group, the cerebral infarction volume of tree shrews in the cerebral ischemia (IS) group and the diabetes complicated with cerebral ischemia (DMIS) group was significantly higher, the neurons were severely damaged, A1 astrocytes were activated, the levels of inflammatory factors interleukin (IL)-1β and IL-6 increased, and mitochondrial autophagy was inhibited. In contrast, in the DMIS + IPOC group, cerebral infarction volume was significantly reduced, neuronal damage was improved, activation of A1 astrocytes and release of inflammatory factors were inhibited, and mitochondrial autophagy was increased. Mechanistically, IPOC activated the brain-derived neurotrophic factor (BDNF)/tropomyosin receptor kinase B (TrkB) pathway and upregulated hypoxia-inducible factor 1α (HIF-1α) expression, which further promoted the expression of Bcl-2/adenovirus E1B 19-kDa-interacting protein 3 (BNIP3).ConclusionIPOC coordinates microglial mitochondrial autophagy and astrocyte inflammatory regulation through the BDNF–TrkB–HIF–1α–BNIP3 signaling cascade, providing a new target for precise intervention in diabetes combined with cerebral ischemia.